A study of the distribution of medical cases and the number of pilgrims visiting King Fahd Hospital in Medina during the Hajj season - Abdulhalem Jan; Zeyad Aljohani; Mohammed Aljuhani; Mansour Alharbi; Abdulaziz Aloufi; Abdulaziz Almusallam; Alaa Abdulrahman Alsayed; Ahmed Aljeraisi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Religious activities that draw large crowds can provide serious public health risks, especially when it comes to the spread of infectious diseases. The Hajj pilgrimage is the biggest annual event hosted by the Kingdom of Saudi Arabia (KSA). The pilgrims are exposed to several health risks when living in close quarters. The study aimed to examine King Fahd Hospital’s patient volume and medical case categories during the Hajj season. Determine the common illnesses that pilgrims present with. Make suggestions for enhancing medical treatment during upcoming Hajj seasons. Methodology: In the Kingdom of Saudi Arabia, a descriptive analytic cross-sectional research design was conducted with the purpose of detecting the distribution of medical cases and the number of pilgrims visiting King Fahd Hospital in Medina during the Hajj season.Aim of the study:To detect the distribution of medical cases and the number of pilgrims visiting King Fahd Hospital in Medina during the Hajj season. Conclusion: Over 10 million pilgrims participate in the Hajj and Umrah each year. For several days, attendees congregate in cramped spaces. There is a huge public health concern when people of different ages, health, susceptibilities to disease, and levels of hygiene sophistication come into close contact. Rapid diagnostic tests, containment techniques, and surveillance are necessary to prevent respiratory illnesses during the Hajj. While the Hajj is unique, similar risks might arise from other large-scale events.